Influence of transient flooding on methane fluxes from subtropical pastures. Issue 3 (29th March 2016) - Chamberlain, Samuel D.; Gomez‐Casanovas, Nuria; Walter, M. Todd; Boughton, Elizabeth H.; Bernacchi, Carl J.; DeLucia, Evan H.; Groffman, Peter M.; Keel, Earl W.; Sparks, Jed P.
Abstract: Seasonally flooded subtropical pastures are major methane (CH4 ) sources, where transient flooding drives episodic and high‐magnitude emissions from the underlying landscape. Understanding the mechanisms that drive these patterns is needed to better understand pasture CH4 emissions and their response to global change. We investigated belowground CH4 dynamics in relation to surface fluxes using laboratory water table manipulations and compared these results to field‐based eddy covariance measurements to link within‐soil CH4 dynamics to ecosystem fluxes. Ecosystem CH4 fluxes lag flooding events, and this dynamic was replicated in laboratory experiments. In both cases, peak emissions were observed during water table recession. Flooding of surface organic soils and precipitation driven oxygen pulses best explained the observed time lags. Precipitation oxygen pulses likely delay CH4 emissions until groundwater dissolved oxygen is consumed, and emissions were temporally linked to CH4 production in surface soil horizons. Methane accumulating in deep soils did not contribute to surface fluxes and is likely oxidized within the soil profile. Methane production rates in surface organic soils were also orders of magnitude higher than in deep mineral soils, suggesting that over longer flooding regimes CH4 produced in deep horizons is not a significant component of surface emissions. Our results demonstrate that distinct CH4 dynamics may be stratified by depth and flooding of surface organic soils drives CH4 fluxes from subtropical pastures. These results suggest that small changes in pasture water table dynamics can drive large changes in CH4 emissions if surface soils remain saturated over longer time scales. Key Points: Transient flooding events drive large and variable methane emissions from subtropical pastures Methane emissions lag water table fluctuations, and peak fluxes occur during water table recession Lags are likely driven by surface soil methane dynamics and oxygen pulses delaying emission onset